2020
DOI: 10.1101/2020.07.02.183756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct lipid profile, low-level inflammation and increased antioxidant defense as a signature in HIV-1 elite control status

Abstract: AbstractHIV-1 elite controllers (EC) are a rare but heterogeneous group of HIV-1-infected individuals who are able to suppress viral replication in the absence of antiretroviral therapy. The mechanisms of how EC achieve undetectable viral loads remain unclear. This study aimed to investigate host plasma metabolomics and targeted plasma proteomics in a Swedish HIV-1 cohort including EC and treatment-naïve viremic progressors (VP) as well as HIV-negative individuals (HC) to get i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…Amino acids (essential and non-essential) as a class were signi cantly decreased in feces of EC and increased in feces of VP relative to HC, further supporting enhanced intestinal absorption/uptake in ECs and impaired absorption in VP. Moreover, our recent study on plasma metabolites in the same cohort identi ed that many amino acids were signi cantly elevated in EC plasma samples relative to VP, which further supports the assumption of impaired amino acid absorption/uptake in VP 15 . Differences can in uence these changes in the dietary intake but since the present cohort lacked extensive dietary data, the study groups were instead matched by several parameters including BMI, sexual practice and general food habit.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Amino acids (essential and non-essential) as a class were signi cantly decreased in feces of EC and increased in feces of VP relative to HC, further supporting enhanced intestinal absorption/uptake in ECs and impaired absorption in VP. Moreover, our recent study on plasma metabolites in the same cohort identi ed that many amino acids were signi cantly elevated in EC plasma samples relative to VP, which further supports the assumption of impaired amino acid absorption/uptake in VP 15 . Differences can in uence these changes in the dietary intake but since the present cohort lacked extensive dietary data, the study groups were instead matched by several parameters including BMI, sexual practice and general food habit.…”
Section: Discussionsupporting
confidence: 62%
“…AhR acts hereby as a transcription factor regulating antimicrobial defense and intestinal immune homeostasis as well as inducing anti-in ammatory responses 32,33 . Interestingly, in our recent study on plasma metabolomics, we also observed an enhancement in antioxidant defense pathways, together with low in ammation levels in EC as compared to VP 15 . Hence, indole and skatol produced by the gut microbiota might support and contribute to EC status by providing an unfavorable intestinal environment for HIV-1 replication in EC.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations